Adherence to practice guidelines for coronary artery bypass graft surgery in Shiraz, Iran - Negar Darvish; Mohammad Ali Ostovan; Mehrdad Askarian (ARYA Atherosclerosis, 2015)
BACKGROUND: There is an increasing tendency to use evidence-based medicine and guidelines among physicians. This is also true for concordance of coronary artery bypass graft (CABG) surgery and guidelines; therefore, we aimed to address the adherence to 2011 American College of Cardiology Foundation (ACCF) and the American Heart Association (AHA) guideline for CABG. METHODS: In this cross-sectional study, we assessed 246 patients who underwent CABG in Shiraz, Iran, during 2011-2012, using a data collecting form provided through studying ACCF/AHA guideline 2011. The patients were categorized into clinical subgroups and then grouped into appropriate, in-appropriate and uncertain classes. Chi-square was used to compare categorical variables and t-test was used for continuous variables. RESULTS: Of the 246 patients, 70.3% were grouped into “Class I,” 12.6% into “Class IIa,” 6.9% into “Class IIb” and 10.2% into “Class III.” Therefore, 82.9% of the patients were grouped into “appropriate,” 6.9% into “uncertain,” and 10.2% into group “inappropriate.” CONCLUSION: We suggest that more attention is needed to be paid to these guidelines. Using these guidelines may help surgeons to have a uniform approach for patients.